2018
DOI: 10.1177/1098612x18773913
|View full text |Cite
|
Sign up to set email alerts
|

Response, disease-free interval and overall survival of cats with nasal planum squamous cell carcinoma treated with a fractionated vs a single-dose protocol of strontium plesiotherapy

Abstract: Objectives The main aim of the study was to establish response, disease-free interval (DFI) and overall survival of cats with nasal planum squamous cell carcinoma (SCC) treated with Sr90 plesiotherapy. A secondary aim was to determine whether a fractionated protocol is more effective than a single-dose protocol in terms of response, DFI and overall survival. The third aim was to evaluate whether we can identify prognostic factors that influence overall survival. Methods This was a retrospective study that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Although a range of different treatments have been used in domestic cats with nasal planum SCC such as strontium (Sr90) plesiotherapy (Berlato et al 2019;Hammond et al 2007), boron neutron capture therapy (Trivillin et al 2008) and intralesional carboplatin and superficial radiotherapy (De Vos, Burm & Focker 2004), radiation therapy remains the most common therapy. Several radiation therapy protocols are in use including a Monday-Wednesday-Friday schedule (Theon et al 1995), hypofractionated (Cunha et al 2010) and accelerated protocols (Gasymova et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although a range of different treatments have been used in domestic cats with nasal planum SCC such as strontium (Sr90) plesiotherapy (Berlato et al 2019;Hammond et al 2007), boron neutron capture therapy (Trivillin et al 2008) and intralesional carboplatin and superficial radiotherapy (De Vos, Burm & Focker 2004), radiation therapy remains the most common therapy. Several radiation therapy protocols are in use including a Monday-Wednesday-Friday schedule (Theon et al 1995), hypofractionated (Cunha et al 2010) and accelerated protocols (Gasymova et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In a more recent study, the two protocols were compared and reported similar results to what had been previously published. 5 A complete response was seen in 74% of the cases with a median disease-free interval of 780 days and a recurrence rate of 17%. The disease-free interval of cats treated with a fractionated protocol was significantly longer; however, response rates and overall survival were not statistically different between the two protocols.…”
Section: Introductionmentioning
confidence: 92%
“…Numerous treatment modalities are available for the management of feline facial SCCs, including comprehensive surgical excision (including nosectomy), cryotherapy, strontium-90 plesiotherapy (Sr-90), photodynamic therapy, topical immunotherapy with imiquimod cream, electrochemotherapy, intralesional chemotherapy and external beam radiation. 411 Treatment of early facial cutaneous SCCs is primarily surgical if feasible. 12 However, surgery for facial cutaneous SCCs, in most cases, is significantly disfiguring, especially for advanced-stage tumours.…”
Section: Introductionmentioning
confidence: 99%